Endodontic treatment of upper premolar with three root conducts – case report (Research, Society and Development, 2023)
Endodontics aims to contain changes in the pulp and periapex, through biomechanical preparation, which, using instruments and irrigating solutions, disinfects the root canals. This work aims to contain a clinical case of endodontic treatment on an upper first premolar with three root canals. The patient came to the clinic complaining of spontaneous pain in the region of tooth 24. In the clinical and radiographic examination, an unsatisfactory restoration and the existence of infiltration were found. After performing the thermal and percussion test, the diagnosis of symptomatic irreversible pulpitis was made. In the first session, coronary access was made, exposing all channels and being able to observe the third channel. After neutralizing the pulp chamber, intracanal medication and provisional medication were placed. In the second session, the root canals were instrumented, obtaining the #35 file and #40 palatal file as a memory instrument for the vestibular canals, as well as the filling of all canals. The existence of three root canals in the upper first premolar is not very prevalent, but it is important that the professional knows about the likely changes in the anatomy, even though these are not constant, as they can alter the success of the pulpectomy. The efficient way to manage this case is based on prior knowledge of the internal anatomy of the teeth and their possible changes, followed by assertive coronary access and contour/convenience, allowing the location of the canals presente.